Effect of Performance Assessment on Employee Career Development at the Human Resources Development Agency of South Sulawesi Province - M. Yusuf Alfian Rendra Anggoro KR (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
The purpose of this study was to determine and analyze effect of performance assessment on employee career development at the Human Resources Development Agency of South Sulawesi Province. When viewed from the type of data, it is certain that this research is a quantitative research. The type of data that will be used in this research is quantitative data. Sources of data used in this study are primary data and secondary data. The population in this study are all employees of the Human Resources Development Agency of South Sulawesi Province. The population used in this study are 103 employees of the Human Resources Development Agency of South Sulawesi Province. The sample in this study are 82 employees. The analytical method in this study uses simple linear regression analysis. The results show that performance assessment has a positive and significant effect on employee career development at the Human Resources Development Agency of South Sulawesi Province.